2017
DOI: 10.1007/s12035-017-0507-5
|View full text |Cite
|
Sign up to set email alerts
|

Translesion Synthesis DNA Polymerase Kappa Is Indispensable for DNA Repair Synthesis in Cisplatin Exposed Dorsal Root Ganglion Neurons

Abstract: In the peripheral nervous system (PNS) in the absence of tight blood barrier, neurons are at increased risk of DNA damage, yet the question of how effectively PNS neurons manage DNA damage remains largely unanswered. Genotoxins in systemic circulation include chemotherapeutic drugs that reach peripheral neurons and damage their DNA. Because neurotoxicity of platinum-based class of chemotherapeutic drugs has been implicated in PNS neuropathies, we utilized an in vitro model of Dorsal Root Ganglia (DRGs) to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 68 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…The University of Texas Medical Branch Institutional Animal Care and Use Committee approved all mouse-handling procedures. Dorsal root ganglion neurons were isolated from 3–4 months old C57BL/6 male mice (Envigo Laboratories, USA) according to established protocols [2527] and as we described [2830]. Briefly, ganglia were collected from all spinal levels, placed in cold dissecting solution (130 mM NaCl, 5 mM KCl, 2 mM KH2PO4, 1.5 mM CaCl2, 6 mM MgCl2, 10 mM glucose and 10 mM Hepes, pH 7.2), incubated with collagenase A (Roche) and trypsin (1 h/37°C) followed by DNase I (Roche), dissociated by 20 gentle triturations and spun (175 g/3 min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The University of Texas Medical Branch Institutional Animal Care and Use Committee approved all mouse-handling procedures. Dorsal root ganglion neurons were isolated from 3–4 months old C57BL/6 male mice (Envigo Laboratories, USA) according to established protocols [2527] and as we described [2830]. Briefly, ganglia were collected from all spinal levels, placed in cold dissecting solution (130 mM NaCl, 5 mM KCl, 2 mM KH2PO4, 1.5 mM CaCl2, 6 mM MgCl2, 10 mM glucose and 10 mM Hepes, pH 7.2), incubated with collagenase A (Roche) and trypsin (1 h/37°C) followed by DNase I (Roche), dissociated by 20 gentle triturations and spun (175 g/3 min).…”
Section: Methodsmentioning
confidence: 99%
“…DRG neurons seeded on coverslips were treated as indicated and fixed in 4% paraformaldehyde as we described [2830]. Cells were permeabilized with 0.1% Triton X-100/0.1% sodium citrate in PBS and incubated with 3% BSA (w/v)/1% Donkey serum (v/v) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…By using plasmids carrying a specific single-site lesion and knocking down TLS polymerases, pol κ activity in combination with pol ζ resulted in error-prone bypass past CP adducts. Research focused on the regulation of pol κ function in eukaryotic cells demonstrated the involvement of pol κ in DNA repair pathways induced by CP and MMC treatment [108,109,110]. TLS across ICLs formed on oligodeoxynucleotides with acrolein-derived crosslinks and on plasmids with trimethylene crosslinks demonstrated that human pol κ carried out accurate incorporation opposite the crosslinked guanine and extended the primer beyond the lesion [111].…”
Section: Fidelity and Selectivitymentioning
confidence: 99%
“…It should be emphasized that these polymerases are often active outside of the S phase [53][54][55][56] when the concentration of dNTPs is even lower than in the S phase [13], which may contribute to more significant incorporation of rNMPs into DNA. We can then speculate that "non-replicative" ribonucleotides may become particularly relevant in post-mitotic cells, such as neurons, where TLS has been recently found to take place [57].…”
Section: Reparative Dna Synthesismentioning
confidence: 92%